ANALISIS PENERIMAAN PAJAK BEA BALIK NAMA KENDARAAN BERMOTOR DI SULAWESI UTARA - Inggrini, Ratu; Morasa, Jenny; Mawikere, Lidia (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
This study aims to find out the acceptance of tax on transfer fees of motor vehicles in North Sulawesi. This study used qualitative research methods. The result of the research revealed that the receipt of Transfer of Motor Vehicle Title I, especially two-wheeled vehicle (R2), experienced the biggest decrease in February 2017 of 22.10% and experienced the biggest increase in July 2107 of 41.65%. For four-wheeled vehicles (R4) experienced the largest decline in December 2017 of 32.32% and experienced the largest increase in July 2107 amounted to 46.29%. then for the acceptance of Transfer of Motor Vehicle Name II II, especially for motorcycles (R2), the biggest decrease in March 2017 was 5.59% and the highest increase was in January 2018 of 112.79%. For four-wheeled vehicles (R4) experienced the largest decrease in April 2017 of 35.65% and experienced the largest increase in October 2017 of 31.24%Keywords : Tax. public service